Sonochemical redox reactions of Pu(iii) and Pu(iv) in aqueous nitric solutions. Issue 6 (15th October 2014) - Virot, Matthieu; Venault, Laurent; Moisy, Philippe; Nikitenko, Sergey I.
Abstract : The 20 kHz sonication of aqueous nitric solutions generates active species which can further react with Pu(iv ) and Pu(iii ) ions. Abstract : The behavior of Pu(iv ) and Pu(iii ) was investigated in aqueous nitric solutions under ultrasound irradiation (Ar, 20 kHz). In the absence of anti-nitrous reagents, ultrasound has no effect on Pu(iv ), while Pu(iii ) can be rapidly oxidized to Pu(iv ) due to the autocatalytic formation of HNO2 induced by HNO3 sonolysis. In the presence of anti-nitrous reagents (sulfamic acid or hydrazinium nitrate), Pu(iv ) can be sonochemically reduced to Pu(iii ). The reduction follows a first order reaction law and leads to a steady state where Pu(iv ) and Pu(iii ) coexist in solution. The reduction process is attributed to the sonochemical generation of H2 O2 in solution. The kinetics attributed to the reduction of Pu(iv ) are however higher than those related to the formation of H2 O2 which, after several hypotheses, is explained by the sonochemical erosion of the titanium-based sonotrode. Titanium particles thereby generated can be solubilized under ultrasound and generate Ti(iii ) as an intermediate species, a strong reducing agent able to react with Pu(iv ).